2022
DOI: 10.17161/kjm.vol15.17592
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities and Determinants of Sufficient Physical Activity Levels

Abstract: Introduction. It is important to identify racial/ethnic groups that may be less likely to achieve sufficient physical activity levels, and to address barriers to meeting physical activity requirements. Methods. Cross-sectional data from the 2006-2015 National Health Interview Survey (NHIS) was used to compare self-reported sufficient physical activity among different racial/ethnic groups: non-Hispanic (NH) Whites, NH Blacks, NH Asians, and Hispanics. Sufficient physical activity was defined as ≥150 minutes per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Where social prescribing is available, relevant exercise programmes could be offered to these SA individuals. Within the community, free gym membership and local physical activity facilities could encourage further positive EPA behaviours [ 69 ]. Additionally, posters and advertisement of gym classes and exercise programmes could picture SA people exercising in their ‘culturally acceptable’ attires.…”
Section: Discussionmentioning
confidence: 99%
“…Where social prescribing is available, relevant exercise programmes could be offered to these SA individuals. Within the community, free gym membership and local physical activity facilities could encourage further positive EPA behaviours [ 69 ]. Additionally, posters and advertisement of gym classes and exercise programmes could picture SA people exercising in their ‘culturally acceptable’ attires.…”
Section: Discussionmentioning
confidence: 99%
“…Patel's research showed that even though the proportion of blacks and Hispanics who have sufficient physical activity is similar, there is a significant difference in the incidence of hypertension among them. In addition, the proportion of whites and Asians who have sufficient physical activity is similar, while whites are more than twice as likely as Asians to have coronary artery disease and atherosclerotic cardiovascular disease [29]. Boyer's study revealed that similar levels of physical activity can reduce all-cause and diabetes-related mortality risk among non-Hispanic whites (and non-Hispanic blacks) but have no effect on Mexican Americans [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…As we discussed above, lifestyle-related morbidities are known to predispose patients to the adverse effects of chemotherapy. It is essential to identify ethnic differences in adopting unhealthy lifestyles to comprehend racial/ethnic disparities in chemotherapy-induced cardiotoxicity [ 177 ].…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Reportedly, ethnic minorities have usually adopted less healthy exercise behaviors than White persons, especially among adults. A study by Patel et al [ 177 ] analyzed physical activity levels among different racial/ethnic groups in the US population. White individuals were considerably more likely to engage in physical activity than Hispanic (40%) and African American people (38%) among 296,802 participants.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
See 1 more Smart Citation